Xanthan or esterified xanthan/cobalt ferrite-lignin hybrid materials for methyl blue and basic fuchsine dyes removal: equilibrium, kinetic and thermodynamic studies. (January 2023) - Apostol, I.; Anghel, N.; Doroftei, F.; Bele, A.; Spiridon, I.
Abstract: In this study, new adsorbents based on xanthan (XG) or esterified xanthan (XGAC) and ferrite-lignin hybrids were obtained and characterized by using the dynamic vapor sorption (DVS) method, infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The porosity, swelling ratio and point of zero charge (PZC) of the adsorbents were also evaluated. Batch adsorption experiments have been performed to determine the adsorption capacity of the adsorbents for Methyl Blue (MB) and Basic Fuchsine (BF). Ferrite-Lignoboost® lignin and ferrite-organosolv lignin hybrid materials (CFLB and CFLO) presented the highest adsorption capacity for MB dye (44.73 and 37.54 mg/g), while the adsorbents based on xanthan and ferrite-lignin hybrids (XG/CFLO and XG/CFLB) retained the highest quantities of BF dye (36.23 and 33.33 mg/g). The chemical nature of the adsorption process was determined, the analyzed data being better fitted to the pseudo second order (PSO) kinetic model. The data analysis showed that the adsorption process followed Langmuir, Dubinin-Radushkevich and Jovanović isotherm models. All the studied adsorption processes were endothermic (ΔH o > 0) and the positive values of the entropy (ΔS o > 0) indicated disorder at the interface between the adsorbent and the dye solutions. Graphical abstract: Image 1 Highlights: Ferrite-Lignoboost® lignin (CFLB) and ferrite-organosolv lignin (CFLO) hybrids were tested for dyes adsorbents. New adsorbents based on xanthan (XG) or esterified xanthan (XGAC) and ferrite-lignin hybrids were obtained and characterized. Unmodified xanthan adsorbents presented a higher water sorption capacity, compared to those containing esterified xanthan. Adsorption process followed Langmuir, Dubinin-Radushkevich and Jovanović isotherm models.